Pengaruh Inflasi Dan Tingkat Pendidikan Terhadap Indeks Pembangunan Manusia Dengan Pertumbuhan Ekonomi Sebagai Variabel Intervening (Di Kabupaten Mandailing Natal Tahun 2018-2023) - Novita Octavia; Isnaini Harahap; Muhammad Ikhsan Harahap (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to analyze the influence and relationship between 4 (four) variables, namely Inflation, education level, human development index and economic growth and test intervening variables as mediating variables between independent variables and dependent variables. This type of research is quantitative research. The data processed was obtained from the Mandailing Natal Regency Statistics Agency. The data obtained was then analyzed using multiple linear regression tests and hypothesis testing using SPSS IBM version 22. The results of this study indicate that the accepted hypothesis is a positive and significant relationship between the three independent variables on the dependent variable. It is obtained that the significance value of X1 is 0.000 <0.05, so it can be concluded directly that there is a significant effect of X1 on Y, the significance value of X2 is 0.008 <0.05, so it can be concluded directly that there is a significant effect of X2 on Y, the significance value of X1 is 0.1>0.05, so it can be concluded directly that there is no significant effect of X1 on Z, the significance value of X2 is 0.5>0.05, so it can be concluded directly that there is no significant effect of X2 on Z, the significance value of Y on Z is 0.8>0.05, so it can be concluded directly that there is no significant effect of variable Y on Z.